Evaluation of Aminoglycosides Consumption in Open Heart Surgery Based on the Defined Daily Dose Index - Golpar Gholizadeh Shirdarreh; Gohar Eslami; Aria Soleimani; Ebrahim Salehifa (Mazandaran University of Medical Sciences, 2020)
Background: Resistance to antibiotics, including aminoglycosides  (AMG) is one of the problems associated with inappropriate administration of broad-spectrum antibiotics. Objectives: This study aimed to assess the clinical features of aminoglycosides consumption based on the Defined Daily Dose (DDD) index in open heart surgery. Methods: This study was done on 268 patients who underwent heart surgery during 2015 and 2016. Clinical and demographic characteristics, laboratory data, and aminoglycoside-related data such as dose and the total duration of administration were collected through a questionnaire designed by the authors. The patients' DDD/100 bed-days were calculated, too. Results: Out of 268 patients, 170 patients (63.4%) were male. The Mean±SD age of the patients was 60.65±10.71 years and the Mean±SD duration of hospitalization was 12.19±7.02 days. Ischemic heart disease was the most prevalent cause of hospitalization. The Mean duration of receiving aminoglycosides was 3.61 days. In 134 patients (50%), creatinine clearance was less than 60 mL/min during aminoglycosides administration. In 25 patients (9.32%), a 50% increase in serum creatinine during receiving aminoglycosides was observed. Creatinine clearance had not been calculated for any patient. Conclusion: In this study, monitoring the side effects of aminoglycosides and the serum concentration was not routinely performed. Dose adjustment of aminoglycosides based on renal function test was not considered in a large number of patients and as a result, the dose was inappropriate in many patients. Therefore, it is recommended that the guidelines of drug usage were followed and the patients were monitored more closely for side effects.